Two-year follow-up of post-traumatic stress disorder symptoms in healthcare workers after the COVID-19 pandemic in China - Hao Chen; Qing Ma; Bo Du; Yan Huang; Shi-Guang Zhu (International Journal of Occupational Medicine and Environmental Health, 2023)
Objectives This study aimed to conduct a 2-year follow-up of mental disorders in healthcare workers (HCWs) in a region of China outside the epidemic’s core zone who happened to be directly or possibly exposed to persons with COVID-19.